Understanding pro-environmental workplace behavior: a comparative study. Issue 9 (30th January 2019) - Tezel, Ecem; Giritli, Heyecan
Abstract : Purpose: This paper aims to fulfill the gap in existing knowledge of determinants of pro-environmental behavior (PEB) in the workplace and the influence of sustainability certificates on occupants' PEBs in workplace settings. Design/methodology/approach: A questionnaire survey with a total of 95 respondents from both certified and noncertified office buildings was conducted. Two independent sample comparisons were executed to understand the influence of sustainable building certificates on occupants' environmental values, beliefs, awareness and PEBs. Findings: Ecocentric value, belief and awareness were found as the predictors of pro-environmental workplace behavior. Certified office occupants showed higher awareness about buildings' environmentally oriented characteristics. Despite higher awareness, certified office occupants revealed less PEB compared to those who work in noncertified office buildings. Originality/value: This study determined the influencing factors on PEBs in workplaces and PEB differences between certified and noncertified building occupants. Less PEBs of occupants in certified offices signify the misperception of individuals about sustainable buildings and the need for more informative training about sustainability issues in the society. This result also draws academic attention to sustainable building evaluation practices and provides certain insights for more occupant integrated evaluation alternative for sustainable buildings.